Core@shell Poly(n‐butylacrylate)@polystyrene Nanoparticles: Baroplastic Force‐Responsiveness in Presence of Strong Phase Separation. Issue 7 (28th January 2016) - Bonetti, Simone; Farina, Matteo; Mauri, Michele; Koynov, Kaloian; Butt, Hans‐Jürgen; Kappl, Michael; Simonutti, Roberto
Abstract : Poly( n ‐butylacrylate)@polystyrene nanoparticles behaving as a capsule‐based sealing nanoadditive are synthesized through an optimized semicontinuous emulsion polymerization protocol. Solid state time‐domain 1 H‐NMR and 13 C magic angle spinning (MAS) NMR analysis suggest strong phase separation. Line width of 13 C resonances in cross polarization and single pulse experiment MAS‐NMR spectra indicates that the peculiar mobility of each phase is preserved at the nanoscale. Atomic force spectroscopy (AFM) shows the permanence of spherical shape in absence of solvent (i.e., subsequent to strong capillary and surface forces) up to moderate external load, as well as the possibility of plastically deforming the polystyrene shell and ultimately triggering the nanoparticle flow at higher force loads. The breakdown characteristic of the nanoparticle shows for the first time baroplastic behavior on a single particle with precise biphasic core@shell morphology. Abstract : Poly(n‐butylacrylate)@polystyrene (PBA@PS) nanoparticles behaving as a baroplastic sealing nanoadditive are synthesized with a semicontinuous emulsion polymerization protocol. Solid state nuclear magnetic resonance indicates strong phase separation between PBA and PS, where the peculiar mobility of each phase is preserved. The two nanophase domains instead display a semi‐solid fluid state during pressure‐induced single‐particle breakdown produced and investigated by atomic force spectroscopy.